Determinan Wasting pada Usia 6-59 Bulan: Indonesia Family Life Survey 2014: Determinants of Wasted Among Age 6-59 Months: The Indonesia Family Life Survey 2014 - Happy Novriyanti Purwadi; Dieta Nurrika; Melisa Wulandari; Herry Novrinda; Hana Febriyanti (Universitas Airlangga, 2023)
Background: Nutritional status is an issue of concern especially in developing countries. The Sustainable Development Goals (SDGs) include a wasting target, namely reducing the proportion of children suffering from wasting to <5% in 2025 and <3% in 2030. In Indonesia, in 2019 and 2021, the prevalence of wasting was 7.4% and 7.1%, respectively. Objectives: The purpose of this study was to determine the determinants of wasting in children aged 6-59 months in Indonesia based on data from the fifth cross-sectional Indonesia Family Life Survey (IFLS) in 2014. Methods: A Cross-sectional study from IFLS 2014 on 2672 children (6-59 months) was conducted. The independent variables were history of acute respiratory infection (ARI), history of diarrhea, frequency of meals, immunization, environmental health, monthly per capita expenditure (PCE), and the location of the child's residence. The dependent variable was wasting, which is measured by weight and height. Data analysis consisted of using the chi-square test. Results: The results showed that there was a significant relationship between environmental health (p-value<0.01), monthly per capita expenditure (p-value<0.01), and the child's place of residence (p-value<0.01) with wasting in children aged 6-59 months. Conclusions: There is a significant relationship between environmental health, monthly per capita expenditure, and location of residence and wasting among children aged 6-59 months. Priorities in making health policies to reduce wasting may differ from region to region.